Health risk assessment of pollutant emissions from coal-fired power plant: a case study in Malaysia - Kamarudin, Mohd Shahril; Zermane, Abderrahim; Mohd Nizam Ong, Nur Aliah Fatin; Ab Rasid, Noorazmin; Masuri, Shafizah; Mohd Tohir, Mohd Zahirasri (Universiti Putra Malaysia Press, 2024)
Coal-fired power plants (CFPPs) are Malaysia’s primary electricity source, but their emissions adversely affect human health, organism growth, climate change, and the environment. The carbon, hydrogen, and sulphur content of coal make it a viable option for electricity generation. However, the by-products from leaching, volatilisation, melting, decomposition, oxidation, hydration, and other chemical reactions significantly negatively impact the environment and human health. This study aims to quantify the emissions from a coal-fired power plant, investigate the interplay between different emissions, simulate the dispersion of emissions, and assess their health impact through a health risk assessment. The results indicate that SO2 is the primary contributor to emissions and its impact on human health is a concern. The health effects, both chronic and acute, are more pronounced in children than in adults. This study combines real-time emissions data and simulations to assess emissions’ health impact, raising awareness about the emissions from coal-fired power plants. Furthermore, the findings can potentially enhance working conditions for employees and promote environmental health.